2002
DOI: 10.1177/009127002401382641
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Erythromycin and Clarithromycin on the Pharmacokinetics of Intravenous Digoxin in Healthy Volunteers

Abstract: Several case reports have suggested an interaction between digoxin and macrolide antibiotics. The authors investigated the effect of erythromycin and clarithromycin on the pharmacokinetics of intravenously administered digoxin (0.5 mg) in healthy subjects. Nine male subjects participated in three studies (digoxin alone, digoxin with erythromycin, and digoxin with clarithromycin). Subjects took erythromycin (800 mg per day) or clarithromycin (400 mg per day) on the day before digoxin dosing and during the kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…In addition, digoxin had a relatively long half-life of over 30 h. The pharmacokinetic profile of digoxin in this study was similar to the previously published reports [17,18]. However, the C max after intravenous administration with the same dosage was slightly higher (13.8 ng/mL) in this study than reported (9.1 ng/mL) in the literature [19], which could be explained by an infusion duration of 30 min instead of the 1 h used in this study.…”
Section: R E T R a C T E Dsupporting
confidence: 87%
“…In addition, digoxin had a relatively long half-life of over 30 h. The pharmacokinetic profile of digoxin in this study was similar to the previously published reports [17,18]. However, the C max after intravenous administration with the same dosage was slightly higher (13.8 ng/mL) in this study than reported (9.1 ng/mL) in the literature [19], which could be explained by an infusion duration of 30 min instead of the 1 h used in this study.…”
Section: R E T R a C T E Dsupporting
confidence: 87%
“…Furthermore, increase in digoxin levels and toxicity have been observed only for orally co-administeration of digoxin and macrolides . Although it was suggested that erythromycin and clarithromycin had different potencies for inhibition of P-gp [18], our results showed no significant difference between the effects of the macrolides which confirm the results of the study conducted by Tsutsumi et al [19] Assuming complete P-gp inhibition by erythromycin, EIR for digoxin was found to be 0.30 -0.44, indicating that 30 -44 % of passive transport of digoxin is attenuated by P-gp-mediated transport. Based on permeability data for digoxin in the presence and absence of clarithromycin, the EIR value is 0.35 -0.54.…”
Section: Discussionsupporting
confidence: 88%
“…However, Tsutsumi et al reported that renal digoxin excretion is not inhibited, but rather enhanced by clarithromycin and erythromycin [6]. On the other hand, it was found in a clinical study that clarithromycin decreased the nonrenal clearance of digoxin, but not the renal clearance [7].…”
Section: Introductionmentioning
confidence: 97%